Anti-vascular endothelial growth factor treatment for choroidal neovascularization secondary to angioid streaks in pseudoxanthoma elasticum: a case report and systemic review - ZhouAiyi; ZhouChenjing; LiuZiyao; QuanYanlong (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
The present study reports a case of a patient with choroidal neovascularization (CNV) associated with pseudoxanthoma elasticum (PXE). We observed the functional and anatomical improvement of the patient treated with intravitreal vascular endothelial growth factor (VEGF) inhibitor bevacizumab. The study also systematically searched the database for similar cases to provide a literature review. Data concerning the clinical features, treatment strategies and outcomes were extracted and analyzed. Retrospective interventional case report and systematic literature review. A 56-year-old healthy Chinese woman with CNV secondary to PXE was reported. Examinations included best corrected visual acuity (BCVA), biomicroscopy, optical coherence tomography (OCT), fluorescein and indocyanine green angiography and digital fundus photography. The patient managed with intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections (bevacizumab 1.25 mg/0.05 mL). The Cochrane Library, PubMed, OVID, and UpToDate databases were searched using the term pseudoxanthoma elasticum or Grönblad-Strandberg syndrome with the limits English. Articles that predated the databases were gathered from current references. Fundus examination revealed angioid streaks bilaterally and CNV in left eye (LE). After the patient underwent three intravitreal injections of bevacizumab, the LE showed absorption of the subretinal fluid and shrinkage of the CNV. Visual acuity (VA) was improved in her treated LE. Bevacizumab treatment was well tolerated with no adverse events reported. Approximately ten articles about 45 patients (49 eyes) describing CNV secondary to angioid streaks in PXE treated with anti-VEGF were found in the literature search. In the present case, bevacizumab of an initial three injection loading dose, achieved maintenance of visual function in the treatment of CNV associated with angioid streaks in PXE. Literature articles concluded that the intravitreal application of anti-VEGF is highly efficient for improving and stabilizing the lesion as well as the eyesight. So we believe that anti-VEGF therapy can be a great choice of treatment for CNV secondary to angioid streaks related PXE.